Economic ev?luation of land in land fund diversification - Мahsudov Muhammadbek Dilshodbek Ugli (International Journal of Financial, Accounting, and Management, 2019)
Purpose: In this article are discussed modern trends in the economic evaluation of land resources. Research Methodology: In carrying out the research work, it is aimed at carrying out the preliminary research work on establishing a system of all land resource utilization in the area. In this, analyzed various economic benefits, measures taken, the experiences of developed countries. Results: As a result of the study, new methods, clear analytical results were obtained in the practice of economic incentives. Limitations: The study was carried out solely on the basis of Statistics and internet data. Contribution: Land use will increase, economic growth will be achieved. The result of the study may be one of the important factors in the achievement of free economic entrepreneurship and free civil society activities. Keywords: Diversification, Land fund, Evaluation, Economic evaluation, Quantitative assessment, Allocation methods